2011
DOI: 10.1002/pon.1782
|View full text |Cite
|
Sign up to set email alerts
|

The combined contribution of social support and coping strategies in predicting post‐traumatic growth: a longitudinal study on cancer patients

Abstract: This study contributes to a deeper understanding of the type of social support that may specifically aid cancer patients in experiencing PTG. Furthermore, findings confirm the important role of problem-focused coping strategies in growing psychologically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
133
6
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(164 citation statements)
references
References 50 publications
21
133
6
4
Order By: Relevance
“…Although the PTGI consists of five subscales tapping on dimensions such as spiritual change and gain in personal strength, in this study we used the inventory as a global measure of PTG because of sample size limitations. This approach, which is consistent with studies that have found the PTGI items to load onto a single factor during exploratory principal component analysis, has been used several times in the literature (e.g., [23,24]). …”
Section: Post-traumatic Growthsupporting
confidence: 65%
“…Although the PTGI consists of five subscales tapping on dimensions such as spiritual change and gain in personal strength, in this study we used the inventory as a global measure of PTG because of sample size limitations. This approach, which is consistent with studies that have found the PTGI items to load onto a single factor during exploratory principal component analysis, has been used several times in the literature (e.g., [23,24]). …”
Section: Post-traumatic Growthsupporting
confidence: 65%
“…In his study, Durak (2007) reported that both social support and personal resources have an indirect effect on PTG via situation perception, cognitive procedures, and coping. Autonomy-supportive caregivers significantly predicted greater PTG (Scrignaro et al, 2010).…”
Section: Discussionmentioning
confidence: 93%
“…In their sample of 131 cancer patients, Scrignaro, Barni, and Magrin demonstrated that perceived support was significantly associated with benefit finding. 27 They suggest that the experience of support that encourages autonomy, competence, and relatedness is an important facilitator of positive growth and benefit finding. It would seem evidence is beginning to support the impact of CAM use on coping and positive treatment outcomes, such as benefit finding.…”
Section: Discussionmentioning
confidence: 99%